The distance and properties of hydrogen clouds in the Leading Arm of the Magellanic System. Issue 1 (8th June 2016) - For, B.-Q.; Staveley-Smith, L.; McClure-Griffiths, N. M.; Westmeier, T.; Bekki, K.
Abstract: We present a high-resolution study of five high-velocity clouds in the Magellanic Leading Arm region. This is a follow-up study of our widefield Parkes survey of the region in order to probe the multiphase structures of the clouds and to give an insight to their origin, evolution and distance. High-resolution data were obtained from the Australia Telescope Compact Array. By combining with single-dish data from the Galactic All-Sky Survey, we are able to probe compact and diffuse emission simultaneously. We identify resolved and unresolved clumps. Physical parameters were derived for both diffuse structure and compact clumps. The latter are cold with typical velocity linewidths of 5 km s −1 . We find a gradient in thermal halo pressure, hydrogen density and H i column density of high-velocity clouds as a function of Galactic latitude. This is possibly the first observational evidence of varying distance in the Leading Arm region, with the leading part of the Leading Arm (LA II and III) probably being closer to the Galactic disc than the trailing end (LA I).